Tough minded faith for tender hearted people - Schuller, Robert H. (Nelson, 1983)
366 motivational messages that make every year a leap year--A leap from self-doubt to self-fulfillment! Turn any day of the year into a tuming point in your life. Dr. Robert H. Schuller, America`s foremost proponent of "possibility thinking" and best-selling author of tough Times Never Last, But Tough People Do! here presents a day-by-day devotional guide designed to release your inner health, energy and power to make the impossible possible. What is Tough Minded Faith ? Sensing success in dark times, prioritizing your possibilities, coming back after defeat, adventuring into new territories, facing the future unafraid, trading off anxiety for peace, standing up for your convictions, assuring yourself of success, and much more. 366 steps in all move and inspire you to turn every negative into a positive, and to make every day the best day of your life. Make the turn to tough-minded faith. . .and make the leap to super-successful living. Your life will never be the same.